EDUCATIONAL REFORM AS AN INSTRUMENT OF ISLAMIC MODERNIZATION: A HISTORICAL STUDY DURING THE ERA OF SULTAN MAHMUD II - Dewi, Nurfitria (Edukasi Islami : Jurnal Pendidikan Islam, 2025)
This study examines educational reform during the reign of Sultan Mahmud II (1808–1839) as a principal instrument of Islamic modernization in the Ottoman Empire. The research is grounded in the context of political, military, and administrative decline in the early nineteenth century, alongside the growing challenges posed by Western modernity. Employing a qualitative approach based on historical research methods, this study analyzes the background of educational reform, the policies implemented, and their socio-religious implications for Ottoman society. Data were collected through extensive library research using primary and secondary sources and analyzed through heuristic, verification, interpretation, and historiographical stages. The findings reveal that educational reform under Sultan Mahmud II was not merely a technical response to Western advancement but functioned as an ideological and structural mechanism for producing a modern state apparatus and a new class of Muslim intellectuals. Despite resistance from conservative religious groups, these reforms played a crucial role in reshaping state–society relations and laid the groundwork for subsequent reforms during the Tanzimat era. This study highlights the strategic role of education in mediating between Islamic values and the demands of modern governance.